Extracellular vesicles as vital players in drug delivery: a focus on clinical disease treatment - Chen, Tiangang; Chen, Dan; Su, Wanting; Liang, Jianlan; Liu, Xiangning; Cai, Mingxiang (Frontiers in Bioengineering and Biotechnology, 2025)
Extracellular vesicles (EVs), a diverse population of bilayer lipid-membrane vesicles secreted by cells, have emerged as ideal drug carriers due to their efficient cellular uptake and targeted delivery capabilities. Advancements in medical and bioengineering collaborations have enabled EVs to be engineered for specific marker expression or therapeutic cargo transport, positioning them as a promising modality for treating cancer, neurological disorders, cardiovascular diseases, and beyond. EV-based drug delivery strategies offer distinct advantages, including facilitation of intercellular communication and immune modulation, high biocompatibility and stability, the ability to traverse the blood-brain barrier, and potential synergistic interactions with encapsulated therapeutics to enhance efficacy. This review explores EV isolation and scalable production, emphasizing cost-effective and reproducible manufacturing strategies, cargo-loading methodologies, and therapeutic applications. Additionally, the current landscape of EV-based targeted drug delivery, clinical translation prospects, and prevailing challenges are examined to provide a comprehensive perspective on their potential in drug delivery systems.